Evaluación del valor nutritivo de las principales materias primas que se utilizan en la alimentación de terneras de 3 - 6 meses de edad en el cantón Cayambe - Coyago Chimarro, Blanca Piedad (2015)
This research deals with the evaluation of the nutritional value of major food sources used in the rearing of calves in the Cayambe canton. The chemical composition of energy and protein raw materials has allowed to know and identify the contents of constituents elements and understand the nutritional quality (protein, fiber, carbohydrates, fat, minerals and vitamins), based on that, the consumption of raw materials, weight gain in kg / day and the cost-benefit relationship were assessed. The results obtained, allowed to analyse the relationship between nutritional quality variables, consumption, weight gain and profit according to the cost of each raw material, this information generates data that guide the decision-making structure rations using energy and protein sources more suitable for rearing calves from 3-6 months old. The small producer seeks to cover the nutritional requirements that enable it to achieve the productive and reproductive objectives in less time and costs, so it is necessary to highlight the importance of raising replacement animals in livestock production systems, especially in the first months of life, since from it depends the future of the herd.